Photoacid behaviour in a fluorinated green fluorescent protein chromophore: ultrafast formation of anion and zwitterion states. Issue 9 (17th June 2016) - Laptenok, S. P.; Conyard, J.; Page, P. C. Bulman; Chan, Y.; You, M.; Jaffrey, S. R.; Meech, S. R.
Abstract : The photophysics of the chromophore of the green fluorescent protein in Aequorea victoria (avGFP) are dominated by an excited state proton transfer reaction. Abstract : The photophysics of the chromophore of the green fluorescent protein in Aequorea victoria (avGFP) are dominated by an excited state proton transfer reaction. In contrast the photophysics of the same chromophore in solution are dominated by radiationless decay, and photoacid behaviour is not observed. Here we show that modification of the p K a of the chromophore by fluorination leads to an excited state proton transfer on an extremely fast (50 fs) time scale. Such a fast rate suggests a barrierless proton transfer and the existence of a pre-formed acceptor site in the aqueous solution, which is supported by solvent and deuterium isotope effects. In addition, at lower pH, photochemical formation of the elusive zwitterion of the GFP chromophore is observed by means of an equally fast excited state proton transfer from the cation. The significance of these results for understanding and modifying the properties of fluorescent proteins are discussed.